Filsafat Islam Sebagai Sumber Kebenaran dan Pengetahuan dalam Pendidikan Agama Islam - Assriatul Sa’adah , Oktaviani; Ari, Jerni; Puspika Sari , Herlini (Program Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah dam Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2024)
In this study, Islamic philosophy is considered as the basis of knowledge and truth in Islamic religious education. Islamic philosophy offers a critical and rational understanding of the concept of truth by citing the thoughts of Islamic philosophers such as Al-Kindi who emphasize the integration of religion and philosophy. This research uses a literature review method which includes relevent books and articles. The results of the analysis show that Islamic philosophy not only helps in the development of science, but also plays an important role in shaping the ethics, morality and character of students. By prioritizing a philosophical approach, Islamic religious education can become more relevant in the modern context and prepare students to respond critically to social and moral problems.